Introduction to transpersonal psychology : bridging spirit and science - Cunningham, Paul F., 1950- (New York, NY : Routledge, 2022)
"Introduction to Transpersonal Psychology: Bridging Spirit and Science provides an accessible and engaging introduction to this complex and evolving field. Adopting a modular approach, the book systematically relates key themes of transpersonal psychology to three major areas within psychology: General psychology, experimental psychology, and clinical psychology. Covering a wide range of topics including transpersonal states of consciousness, biological foundations, research methods, and cognition, the book also features extensive discussion of transpersonal theorists, and the impact of their work on our understanding of psychological concepts. The book also introduces contemporary developments in the field and anticipates future advances such as feminist perspectives and cross-cultural approaches alongside practical experiments designed to give transpersonal theories and concepts psychological roots. A critical evaluation of both mainstream and transpersonal theories and research is applied throughout to foster analytical skills and encourage critical and scientific thinking about humanity's nature as spiritual creatures and ways to educate for personal and social transformation. Accompanied by an online instructor's manual, this book will be an essential companion for all students of Transpersonal or Humanistic Psychology, or those interested in applying transpersonal ideas to mainstream psychological research. Paul"--
Keywords: Humanistic psychology; Mind and body; BODY, MIND & SPIRIT / Parapsychology / General; BODY, MIND & SPIRIT / Spiritualism; PSYCHOLOGY / General